Effectiveness of Solution with 5% Detergent for Cleaning Transnasal Esophagogastroduodenoscopy Lens - Yoshinori Komazawa (Clinical Endoscopy, 2021)
Background/Aims Unsedated transnasal esophagogastroduodenoscopy (EGD) is affected by a poor scope lens-cleaning function. We have previously reported good, albeit limited, effects of an oolong tea washing solution; here, we evaluated the effectiveness of a 5% lens cleaning solution for cleaning an EGD lens. Methods Five percent lens cleaning solution (C), 5% dimethicone solution (D), and distilled water (W) were prepared. Study I: Lenses were soiled with pork grease, washed with each washing solution, and their image quality was judged. Study II: Patients (n=996) scheduled for transnasal EGD were randomly assigned to the C- or W-group. Lens cleanliness level, washing solution volume used, and endoscopist stress due to lens contamination were determined. Results Study I: The image quality of the lenses washed with (C) was significantly superior. (D) was clinically unsuitable because of spray nozzle clogging. Study II: Lens cleaning in the C-group was significantly superior (p<0.0001) and the solution volume required was significantly reduced (p<0.0001), while endoscopist stress was also lower (p<0.0001). Conclusions For transnasal small-caliber EGD, the present 5% lens cleaning solution provided good visibility. It features a high detergency level and is simple to formulate for therapeutic endoscopy applications, such as endoscopic submucosal dissection.